2020
DOI: 10.3390/insects11050281
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Transferrin Expression Enhances the Susceptibility of Plutella xylostella to Isaria cicadae

Abstract: Transferrins (Trfs) are multifunctional proteins with key functions in iron transport. In the present study, a Trf (PxTrf) from Plutella xylostella was identified and characterized. The PxTrf consisted of a 2046-bp open reading frame, which encoded a 681 amino acid protein with a molecular weight of 73.43 kDa and had an isoelectric point of 7.18. Only a single iron domain was predicted in the N-lobe of PxTrf. Although PxTrf was expressed ubiquitously, the highest levels of expression were observed in the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…In our study, we did find expression of the ferritin subunit (LOC113510018), ferritin lower subunit (LOC113510017) and transferrin (LOC113509694) at all time points investigated. However, in contrast to what was seen in other fungal infections, expression levels did not significantly alter during infection (40). Transferrin and ferritin protein levels previously measured in the same G. mellonella infection model, on the other hand, were differentially abundant.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study, we did find expression of the ferritin subunit (LOC113510018), ferritin lower subunit (LOC113510017) and transferrin (LOC113509694) at all time points investigated. However, in contrast to what was seen in other fungal infections, expression levels did not significantly alter during infection (40). Transferrin and ferritin protein levels previously measured in the same G. mellonella infection model, on the other hand, were differentially abundant.…”
Section: Discussioncontrasting
confidence: 75%
“…The diamondback moth, Plutella xylostella , was reared as previously described 16 . Briefly, the larvae of P. xylostella were fed with bok choy ( Brassica rapa chinensis ) seedlings at 25 ± 1 °C, 75 ± 5% relative humidity and a 16 h:8 h (light:dark) photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), a notorious pest of brassicaceae crops, has evolved serious resistance to various classes of insecticides and biopesticides. [14][15][16] Entomopathogenic fungi cause many insect diseases and have been developed as eco-friendly alternatives to chemical insecticides in pests biocontrol, especially for insecticide-resistant insects. 17 Therefore, insect immune response to fungal infection has attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated its ability to enhance immune regulation activity, reduce inflammation, and inhibit tumor growth ( Layland et al, 2014 ; Wei et al, 2016 ; Meng et al, 2019 ; Nxumalo et al, 2020 ). In addition, several studies have demonstrated the potential of C. cicadae as a microbial insecticide against various insects, such as aphids ( Xu et al, 2020 ). Its natural composition is akin to that of Cordyceps sinensis , with active components primarily comprising polysaccharides, nucleosides, sterols, fatty acids and their derivatives, polyphenols, etc.…”
Section: Introductionmentioning
confidence: 99%